Work councils in Germany and the Netherlands compared: An explorative study using an input-throughput-output approach - Annette van den Berg; Yolanda K. Grift; Saraï Sapulete; Wolfram Brehmer; Martin Behrens; Arjen van Witteloostuijn (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2019)
This study provides information on the co-determination practices of German and Dutch works councils. We present the findings of two large-scale works councils' surveys in each country. Where do works councils in Germany and the Netherlands show similarities and where do they show differences? To address this question our study investigates practices of employee representation within the private sector in both countries. By employing an input-throughput-output approach we pursue a detailed analysis of works councils' structures, practices, as well as the outcomes of interest representation. While previous studies, mostly by way of comparing formal institutions, consider works councils in Germany and the Netherlands to be fairly similar, our analysis finds some remarkable differences.
urn:nbn:de:101:1-2019022611285075165963
Keywords: 330; Betriebsrat; Mitbestimmung; Vergleich; Deutschland; Niederlande